A new species of Haliotis (Gastropoda) from São Tomé & Príncipe Islands, Gulf of Guinea, with comparisons to other Haliotis found in the Eastern Atlantic and Mediterranean - Owen, Buzz (Zootaxa, 2014)
The Haliotidae from the Gulf of Guinea, West Africa are reviewed. The distribution of the mainland species Haliotis marmorata Linnaeus, 1758 is confirmed and compared to the insular species from the island nation of São Tomé and Príncipe which is described as Haliotis geigeri n. sp. Both species are illustrated and compared to the other known Haliotidae from the eastern Atlantic.